The Role of Academic Advisors in the Development of Student Human Resource Competencies - Rafikha Anggraini; Nopa Dwi Saputra; Triono Triono (Trescode Green Organization, 2025)
This study aims to explore the role of academic advisors in the development of student human resource (HR) competencies at the Muhammadiyah Institute of Technology, Sumatra. Academic advisors play a key role in supporting students' academic and career development, yet this role is often overlooked in the context of professional competency development. This research employs a qualitative approach using a case study method, involving in-depth interviews with academic advisors, students, and other relevant stakeholders at the institute. The findings reveal that academic advisors not only provide academic guidance but also mentor students in developing non-academic skills, such as communication, time management, and other professional skills. Academic advisors also play a role in connecting students with internship opportunities and professional networks, contributing to their job readiness. However, this study also identifies several challenges, including a lack of training for academic advisors and heavy workloads. The study recommends the need for specialized training for academic advisors and the enhancement of support mechanisms to improve the effectiveness of their role in developing student HR competencies. The results of this research are expected to provide insights for higher education institutions to improve academic advising programs and more effectively support student competency development.